Impaired lung function and serum leptin in men and women with normal body weight: a population based study. Issue 8 (28th July 2003) - Sin, D D; Man, S F P
Abstract : Background: Impaired lung function is a risk factor for cardiovascular morbidity. Whether circulating factors are responsible for this association is unknown. A study was undertaken to determine whether leptin, a hormone that can promote atherothrombosis, is raised in individuals with impaired lung function. Methods: Data from non-obese participants in the Third National Health, Nutrition, and Examination Survey (n=2808) were analysed to determine the relationship between circulating leptin levels and forced expiratory volume in 1 second (FEV1 ) values divided into quintiles (quintile 1, FEV1 predicted ⩽85.2%; quintile 2, 85.3–94.3%; quintile 3, 94.4–101.4%; quintile 4, 101.5–110.0%; and quintile 5, ⩾110.1%). Results: Serum leptin levels changed along the FEV1 gradient. The highest leptin levels were found in quintile 1 (geometric mean (GM) 5.42; interquartile range (IQR) 3.00–9.60 fg/l) and the lowest in quintile 5 (GM 4.94; IQR 2.80–9.10 fg/l). Adjustments for age, body mass index, and other confounders strengthened this relationship. Compared with quintile 5, the odds of having an increased serum leptin level in quintiles 1, 2, 3, and 4 were 2.26 (95% confidence interval (CI) 1.54 to 3.31), 2.20 (95% CI 1.52 to 3.17), 1.46 (95% CI 1.01 to 2.09), and 1.28 (95% CI 0.90 to 1.83), respectively. Conclusion: Individuals with impaired lung function have raised serum leptin levels. Leptin may play a role in the pathogenesis of cardiovascular morbidity and mortality related to impaired lung function.